Functional anatomy and disparity of the postcranial skeleton of African mole-rats (Bathyergidae) - Montoya-Sanhueza, Germán; Bennett, Nigel C.; Chinsamy, Anusuya; Šumbera, Radim (Frontiers in Ecology and Evolution, 2022)
Different aspects of the biology of African mole-rats (Bathyergidae) are well-documented. However, much less investigated are the burrowing adaptations of their appendicular systems. Because bathyergids exhibit different digging modes (scratch-digging and chisel-tooth digging) and social systems (from solitary to highly social), they are a unique group to assess the effects of different biomechanical regimes and social organization on morphology. In this study, we investigate the morphological diversity and intraspecific variation of the appendicular system (forelimb and hindlimb) of a large dataset including seven species of all six bathyergid genera. We hypothesized that scratch-diggers (e.g. Bathyergus) would exhibit a more specialized skeletal phenotype favoring powerful forelimb digging as compared to the chisel-tooth diggers (which do not use their limbs to break up soils), and that among chisel-tooth diggers, the social species will exhibit decreased limb bone specializations as compared to solitary species, due to colony members sharing the effort of digging. Stylopodial (femur, humerus) and zeugopodial (ulna, tibia-fibula) bones of 244 adults of both sexes, and 17 morpho-functional indices that reflect the fossorial ability of the appendicular system were analyzed by multivariate and ordination approaches. Our results show that most bathyergids share a set of highly specialized fossorial features, e.g. a distally located deltoid tuberosity, robust humerus, wide humeral epicondyles, robust ulna, enlarged olecranon process, robust femur and distally fused tibia-fibula. However, the limb phenotype of Heterocephalus glaber showed a reduced fossorial ability, lacking a projected deltoid tuberosity, distal tibio-fibular fusion and generally slender bones. The multivariate analysis revealed significant differences among species, which are discussed according to their social system and digging mode. Our data suggest that despite our expectations, chisel-tooth diggers are equally, or more specialized than scratch-diggers, probably to maximise burrowing in harder soils, although social chisel-tooth diggers may not strictly require extreme specializations (e.g. H. glaber). Indices associated with locomotor advantage showed more symmetrical intralimb and interlimb proportions as compared to surface-dwelling mammals, suggesting increased ability for equal bidirectional locomotion within burrows. Additionally, most of the morphological variation was associated with zeugopods, while the stylopods were more similar among species.